2019
DOI: 10.3390/g10010012
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchy, Power, and Strategies to Promote Cooperation in Social Dilemmas

Abstract: Previous research on cooperation has primarily focused on egalitarian interactions, overlooking a fundamental feature of social life: hierarchy and power asymmetry. While recent accounts posit that hierarchies can reduce within-group conflict, individuals who possess high rank or power tend to show less cooperation. How, then, is cooperation achieved within groups that contain power asymmetries? To address this question, the present research examines how relative power affects cooperation and strategies, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Recent work has found that people's perceptions of interdependence in social situations are organized along these three dimensions (Gerpott et al, 2018 Thompson & Hastie, 1990), and that people understand when they possess relatively high or low power in social interactions (Fiske, 2010;Galinsky et al, 2015;Molho, Balliet, & Wu, 2019;Sivanathan, Pillutla, & Murnighan, 2008). Thus, perceptions of interdependence can be meaningfully tied to the underlying, objective interdependence in social interactions, and so people should share similar inferences about the interdependence that characterizes a specific situation (Balliet et al, 2017).…”
Section: Agreement and Accuracy In Subjective Interdependencementioning
confidence: 99%
“…Recent work has found that people's perceptions of interdependence in social situations are organized along these three dimensions (Gerpott et al, 2018 Thompson & Hastie, 1990), and that people understand when they possess relatively high or low power in social interactions (Fiske, 2010;Galinsky et al, 2015;Molho, Balliet, & Wu, 2019;Sivanathan, Pillutla, & Murnighan, 2008). Thus, perceptions of interdependence can be meaningfully tied to the underlying, objective interdependence in social interactions, and so people should share similar inferences about the interdependence that characterizes a specific situation (Balliet et al, 2017).…”
Section: Agreement and Accuracy In Subjective Interdependencementioning
confidence: 99%
“…According to a vast literature, cooperation can be promoted using different tools, such as punishment [13,14], reputation and gossip [14][15][16], and communication [17]. Of particular relevance is the work of [18], which focuses on cooperation in situations with power asymmetry, testing some strategies that might help promoting cooperation (such as gossip and punishment). The authors show that despite the difference in power, group members do not show significantly different levels of cooperation.…”
Section: Related Literaturementioning
confidence: 99%
“…Fifth, when sampling gossip events in both workplace settings and daily life, researchers should include formal situations (see Figure 3 for examples, for more examples see also, e.g., Dores Cruz et al, 2020). Vignette studies could include formal gossip situations, and experimental studies could offer different communication channels ranging in (in)formality to examine when and why people opt for more formal or informal gossip, for example, as a function of role or power differences (Jeuken et al, 2015; Martinescu et al, 2019a; Molho, Balliet, & Wu,2019; Shank et al, 2019; Wu et al, 2016a). This could provide insights into the dynamics between leaders and subordinates, which could be characterized by gossip on the more formal end of the (in)formality axis.…”
Section: Applying the Dimensional Scaling Framework In Future Researchmentioning
confidence: 99%